Autonomous Surface Reconciliation of a Liquid‐Metal Conductor Micropatterned on a Deformable Hydrogel. Issue 37 (2nd August 2020) - Park, Jung‐Eun; Kang, Han Sol; Koo, Min; Park, Cheolmin
Abstract: Spreading liquid droplets on solid surfaces is a core topic in physical chemistry with significant technological implications. Liquid metals, which are eutectic alloys of constituent metal atoms with low melting temperatures, are practically useful, but difficult to spread on solid surfaces because of their high surface tension. This makes it difficult to use liquid metals as deformable on‐board microcircuitry electrodes, despite their intrinsic deformability. In this study, it is discovered that eutectic gallium–indium (EGaIn) can be spread onto the surface of chemically cross‐linked hydrogels consisting of aliphatic alkyl chains with numerous hydroxyl groups (OH), thus facilitating the development of directly micropatterned EGaIn electrodes. More importantly, EGaIn patterned on a hydrogel autonomously reconciliates its surface to form a firm hydrogel interface upon mechanical deformation of the hydrogel. This autonomous surface reconciliation of EGaIn on hydrogels allows researchers to reap the benefits of chemically modified hydrogels, such as reversible stretching, self‐healing, and water‐swelling capability, thereby facilitating the fabrication of superstretchable, self‐healable, and water‐swellable liquid‐metal electrodes with very high conductance tolerance upon deformation. Such electrodes are suitable for a variety of deformable microelectronic applications. Abstract : Micropatternable, superstretchable, self‐healable, and water‐swellable liquid‐metal electrodes are developed with a low resistance of ≈2 and ≈4.6 Ω at strains of 0% and 1500%, respectively, with low variation in conductance (a variation factor of ≈2.3) by utilizing autonomous surface reconciliation of EGaIn on chemically modified hydrogels. These electrodes are suitable for a variety of deformable microelectronic applications.